2023
DOI: 10.1111/odi.14568
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in developmental defects of enamel: A scoping review

Abstract: ObjectivesThe significant role of epigenetics has been revealed in normal enamel formation process and occurrence of developmental defects. This presented literature is aiming at summarizing the regulatory function of epigenetics in physiological amelogenesis process and reviewing the epigenetic mechanisms in occurrence of developmental defects of enamel (DDE), so as to provide biological foundation evidence to support early predication and clinical management of DDE.MethodAn extensive literature review was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Furthermore, although not signi cant, we found that the use of supplements before and in early pregnancy was associated with lower odds of more severe CL/P. This follow previous studies showing that an association between NSOFC and maternal nutritional de ciencies during early pregnancy [41] Vitamin B and folic acid supplementation were previously reported to be associated with lower risk of NSOFC in infants [42]. Also, an animal study on mice with CP mutation (Tgf-B3-/-) found that folic acid supplementation signi cantly minimized CP severity by improving palatal shelf adhesion and disposition of collagen IV, cytokeratin-17, laminin, and bronectin [43].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, although not signi cant, we found that the use of supplements before and in early pregnancy was associated with lower odds of more severe CL/P. This follow previous studies showing that an association between NSOFC and maternal nutritional de ciencies during early pregnancy [41] Vitamin B and folic acid supplementation were previously reported to be associated with lower risk of NSOFC in infants [42]. Also, an animal study on mice with CP mutation (Tgf-B3-/-) found that folic acid supplementation signi cantly minimized CP severity by improving palatal shelf adhesion and disposition of collagen IV, cytokeratin-17, laminin, and bronectin [43].…”
Section: Discussionsupporting
confidence: 90%
“…This special issue comprises nine invited reviews from OGDRD committee members, focusing on congenital dental abnormalities such as hereditary enamel and dentin defects (Dong et al, 2023; Su et al, 2023; Yuan et al, 2023; Zhang et al, 2023), tooth agenesis (Lan et al, 2022), multiple idiopathic cervical root resorption (Wang et al, 2022), craniofacial and oral malformations including non‐syndromic skeletal Class III malocclusion (Zhou et al, 2022), mandibular coronoid process hyperplasia (Wang, 2022), and hemifacial microsomia (Luo et al, 2023).…”
mentioning
confidence: 99%
“…In the case of hemifacial microsomia, Luo et al (2023) introduced the OMENS‐Plus classification system to enhance the accuracy of diagnosis and optimize treatment approaches (Luo et al, 2023). Reports demonstrate that molecular‐based enamel or dentin phenotypes may provide valuable insights for the precise diagnosis (Dong et al, 2023; Su et al, 2023; Zhang et al, 2023) and clinical management at different stages of dentin dysplasia to avoid the development of secondary dental lesions (Yuan et al, 2023). Part of syndromic dentin defects have the phenotypes similar to dentinogenesis imperfecta or dentin dysplasia, while others do not.…”
mentioning
confidence: 99%
See 1 more Smart Citation